2021
DOI: 10.1136/annrheumdis-2021-eular.1486
|View full text |Cite
|
Sign up to set email alerts
|

Pos0664 a Multicenter Randomized Study in Rheumatoid Arthritis to Compare Iguratimod, Methotrexate, or Combination: 52 Week Efficacy and Safety Results of the Smile Trial

Abstract: Background:Iguratimod (IGU) has demonstrated efficacy and safety for active rheumatoid arthritis (RA) patients in double-blind clinical trials in China and Japan as a new disease-modifying anti-rheumatic drug (DMARD). There are no studies evaluating the radiographic progression of structural joint damage of IGU for the treatment of RA using the mTSS as the primary endpoint.Objectives:Our study was to evaluate the efficacy and safety of IGU monotherapy and IGU combined methotrexate (MTX) compared with MTX monot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…IGU + MTX does not increase the risk of leukopenia, but it can decrease the risk of LFTs. Recently, a multicenter, randomized, double-blind, parallel controlled trial of rheumatoid arthritis showed no significant difference in the incidence of adverse events after weeks of treatment with IGU alone or in combination with MTX compared to MTX (Du et al, 2021). Another study showed that IGU combined with MTX is safer than LEF combined with MTX (Tian et al, 2020).…”
Section: Safety Of Igu or Igu + Mtxmentioning
confidence: 99%
See 2 more Smart Citations
“…IGU + MTX does not increase the risk of leukopenia, but it can decrease the risk of LFTs. Recently, a multicenter, randomized, double-blind, parallel controlled trial of rheumatoid arthritis showed no significant difference in the incidence of adverse events after weeks of treatment with IGU alone or in combination with MTX compared to MTX (Du et al, 2021). Another study showed that IGU combined with MTX is safer than LEF combined with MTX (Tian et al, 2020).…”
Section: Safety Of Igu or Igu + Mtxmentioning
confidence: 99%
“…IGU is a new type of small-molecule compound, which mainly regulates the immune system, inhibits T-cell and B-cell differentiation, reduces inflammatory factors, improves the function of joint swelling, and is widely used in China and Japan (Jiang et al, 2020). Multiple studies have demonstrated the superior efficacy of IGU alone or in combination with MTX in treating RA with acceptable safety (Ishiguro et al, 2013;Shi et al, 2015;Du et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation